THE ROLE OF MINANGKABAU WOMEN IN FAMILY AND COMMUNITY IN GENDER FAIR DEVELOPMENT - Gisha Dilova; Muhammad Syukron; Siti Anisa Siregar; Alfiyyah Nur Hasanah (STIH Putri Maharaja, 2022)
The structure of Minangkabau society is organized based on matrilineal principles according to maternal lineage. Mother in Minangkabau tradition is known as Bundo Kanduang. The recent situation in Kenagarian Ampang Kuranji, the role of women in development can be seen from the existence of PKK women and also inseparable from the role of Bundo Kanduang in a tribe, but the program carried out by Bundo Kanduang has not fully directed policies in terms of education, as well as social for generations of children and even teenagers such as there are still many early marriages, drugs, riots, theft which is increasingly happening. This study aims to examine and analyze the role of Minangkabau women in the family and society in gender-just development in Kenagarian Ampang Kuranji, Koto Baru District. This study uses a sociological/empirical juridical approach. This approach is done by collecting primary data as the main data. The results of his research are that the role of Bundo Kanduang has begun to be felt by the surrounding community, because Bundo Kanduang's participation takes an important part in the development of the nagari through programs that have been carried out well before, but in the future the Bundo Kanduang Institute and the Nagari Ampang Kuranji Government are more pay attention again to mainstreaming women in Kenagarian Ampang Kuranji to achieve gender justice.